Energy absorption of aluminium & steel tubes when compressed in uni-direction with quasi-static load between two flat plates. (2022) - Manjunatha, G.; Bharath, V.G.; Dilip Kumar, K.
Abstract: In different engineering applications usage of Circular Aluminium & Mild Steel tubes as impact energy absorbers is encouraged. Impact energy absorbers (IEA) are one shot devices. In case of any accident or collision, kinetic energy emitted is dissipated with impact energy absorbers to minimize causality. Capacity of energy absorption during dynamic load conditions is high. Current study provides an insight on behavior of energy absorbers during axial load under quasi-static. Various stages of deformation of aluminium & steel tubes when compressed in uni-direction with quasi-static load between two flat plates is observed and energy absorption is calculated.